Through which channels can remittances spur economic growth in MENA countries? - Sami Ben Mim; Mohamed Sami Ben Ali (Kiel Institute for the World Economy (IfW), 2012)
This paper studies the remittances' effect on economic growth. Using panel data techniques, the authors estimate several specifications to provide support of such relationship for MENA countries over the period 1980-2009. The findings provide new robust evidence on how remittances are used in MENA countries and show the main channels which may interfere in this process. Estimation outcomes show that the most important part of remittances is consumed and that remittances stimulate growth only when they are invested. Moreover, empirical results suggest that remittances can enhance growth by encouraging human capital accumulation. Human capital is therefore an effective channel through which remittances stimulate growth in MENA countries.
Keywords: E21; F21; G22; J61; O16; 330; Workers' remittances; economic growth; panel data; MENA zone; Rücküberweisung (Migranten); Wirtschaftswachstum; Bildungsinvestition; Schätzung; MENA-Staaten